ANALYSE DER SELBSTEVALUATION IM LEHRWERK NETZWERK A1 - Habib Mochamad Fachrezy, - (2020)
In German learning, learners are advised to master the 4 language skills, vocabulary and grammar. To improve and assess German language skills a learner needs an evaluation tool. One evaluation tool that can be used by learners is self-evaluation (Selbstevaluation), which is contained in a teaching materials. With Selbstevaluation learners can find out how far they are learning and understanding learning material. But there are still many learners who disregarded the Selbstevaluation, because they don't know the function of the Selbstevaluation itself. This study aims to find out: (1) the structure of Selbstevaluation, (2) the language skills which are contained in the Selbstevaluation, (3) the suitability of Selbstevaluaton's general description in the Netzwerk A1 teaching material book with GER (Gemainsamer Europäischer Referenzrahmen für Sprachen), and (4) the form of Hilfestellung. The method used in this research is descriptive qualitative method. The data analyzed were sourced from the Netzwerk A1 teaching material, namely the Selbstevaluation in Arbeitsbuch. From the analysis it is known that: (1) In each chapter on Arbeitsbuch Netzwerk A1 which consists of 12 chapters, there is Selbstevaluation which is located on the second page before the end of each chapter. Selbstevaluation has several components, namely Kann-Beschreibungen, Hilfestellungen and die Kontrolle des Lernerfolgs mit Emoticons, whose numbers are different in each chapter. (2) The language skills contained in Selbstevaluation consist of listening skills (Hörverstehen), speaking (Sprechfertigkeit), reading (Leseverstehen) and writing (Schreibfertigkeit). (3) The Kann-Beschreibung contained in the Selbstevaluation corresponds to the Kann-Beschreibung in the GER at A1 level, in addition there are also 50 Kann-Beschreibung on A2 level, and 27 Kann-Beschreibung on B1 level. (4) The Hilfestellung which is contained in Selbstevaluation is in the form of instructions which function as a mediator, to indicate the location of exercises in Kursbuch and Arbeitsbuch. Therefore learners are advised to make optimal use of Selbstevaluation in order to develop their language skills.